Lactobacillus fermentum LLB3 improves antioxidant activity of bitter melon (Momordica charantia) (Microbiology Indonesia, 2018)
Oxidative stress plays a major role in the pathogenesis and progression of diabetes. Functional foods with an antioxidant effect can repress oxidative stress. Momordica charantia (bitter melon) contains substances with antidiabetic properties such as charantin, vicine, and polypeptide-p, as well as other unspecific bioactive components such as antioxidants. Lactobacillus fermentum LLB3 isolated from bamboo shoot pickle was used to ferment bitter melon juice. The aim of this study was to evaluate changes in antioxidant activity of bitter melon juice during fermentation. Study has been carried out by fermenting bitter melon juice with L. fermentum LLB3. The free radical scavenging activity of the phenolics were done using 2,2-diphenyl- 1-picrylhydrazyl (DPPH). Antioxidant activity of bitter melon juice increased during 24 hours fermentation. In addition, the sugar content and pH decreased compared with the baseline value. The fermentation of bitter melon juice by L. fermentum LLB3 increased its antioxidant activity. These result suggest that fermented bitter melon juice is a promising agent for diabetes management.